Polypharmacy and factors associated with their prevalence among older patients attending a geriatric centre in South-West Nigeria (2018)
Background: Polypharmacy among older people in Nigeria are prominent issues of public health dimension. Polypharmacy especially in older people with multiple diseases often results in poor health status and outcomes. Objectives: To determine the prevalence and factors associated with polypharmacy among older patients attending the geriatric clinic. Methods: Cross sectional study of 400 elderly patients aged 60 years and above who presented at geriatric clinic, UCH, Ibadan. Polypharmacy was taken as concurrent consumption of =5 medications. Sociodemographic characteristics, lifestyle habits, attitudinal factors on medication understanding, medication pattern and intake were assessed through a questionnaire. Bivariate and multivariate analyses were carried out using SPSS 20 and alpha was set at 0.05. Results: Mean age of the respondents was 70.2 ± 5.9 years and 240 (60.0%) were females. The point prevalence of polypharmacy was 23.8%. The averagemedications consumed were 4 without sex difference. Logistic regression analysis showed that taking too many prescription medications (OR = 2.188; 95% CI = 1.014 – 4.808, p = 0.05), intentionally skipping my medications because they are too many (OR = 3.756; 95% CI = 1.354 – 10.424, p = 0.01) and receiving prescriptions from more than one physicians on regular basis (OR = 2.336; 95% CI = 1.058 – 5.155, p = 0.04) were the most significant factors associated with polypharmacy. Conclusion: Polypharmacy is common among older people in this setting. Healthcare workers should address the attitudinal, social and health related factors, which could lead to polypharmacy.